2023
DOI: 10.20396/bjos.v22i00.8667270
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of salivary opiorphin in oral lichen planus

Abstract: Opiorphin is a pentapeptide, which could be isolated from human fluids and has a decreasing effect on pain. Aim: Since lichen planus is a chronic mucocutaneous disease, which causes pain or burning feeling in the oral mucosa, this study aimed to compare salivary opiorphin levels of oral lichen planus (OLP) patients with healthy subjects. Methods: This case-control study, was performed on 24 patients with OLP lesions and 21 healthy subjects. After collecting unstimulated saliva, opiorphin levels were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some studies report a correlation between opiorphin levels and age (Nejad et al, 2020; Paszynska et al, 2022) or gender (Dufour et al, 2013). However, most studies did not indicate correlation between opiorphin levels and age and gender (Boucher et al, 2017; Dalirsani et al, 2023; Ozdogan et al, 2019, 2020; Salarić et al, 2017). In accordance with the majority of the studies, no significant correlation was observed between opiorphin levels and age and gender in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies report a correlation between opiorphin levels and age (Nejad et al, 2020; Paszynska et al, 2022) or gender (Dufour et al, 2013). However, most studies did not indicate correlation between opiorphin levels and age and gender (Boucher et al, 2017; Dalirsani et al, 2023; Ozdogan et al, 2019, 2020; Salarić et al, 2017). In accordance with the majority of the studies, no significant correlation was observed between opiorphin levels and age and gender in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence strongly suggests that secretion of opiorphin in biological fluids increases as a response to painful stimuli, likely as a defense mechanism to increase the potency of innate anti‐nociceptive mechanisms. While some of these studies report a correlation between the opiorphin levels and the severity of the pain (Al‐Saffar et al, 2013; Ozdogan et al, 2019; Parida et al, 2018), majority of the studies report no correlation (Boucher et al, 2017; Dalirsani et al, 2023; Nejad et al, 2020; Ozdogan et al, 2020; Salarić et al, 2017). In our study, no significant correlation between the VAS scores and opiorphin levels was observed as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation